Peran Pendidikan Lingkungan dalam Membentuk Pola Konsumsi yang Bertanggung Jawab di Kalangan Mahasiswa - Dini Anggraini; Rifauziah Arni Malau; Zohya Azzura (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
This study aims to analyze the role of environmental education in shaping responsible consumption patterns among university students. Using a qualitative approach, data were collected through in-depth interviews with several students from different faculties who were involved in environmental-based activities such as green campus programs and environmental education courses. The results show that environmental education plays a significant role in increasing environmental awareness and encouraging behavioral change toward sustainable consumption. Students who participated in environmental learning activities demonstrated greater awareness in reducing single-use plastic, conserving energy, and choosing eco-friendly products. However, some respondents argued that the impact of environmental education is limited when it remains theoretical and lacks practical implementation. The findings emphasize that the effectiveness of environmental education depends on the integration of theory, practice, and supportive campus culture. Therefore, universities should strengthen environmental education through experiential learning, environmental campaigns, and sustainable campus facilities to foster students’ environmental responsibility and long-term sustainable behavior.